0316 Emotion Regulation During Sleep Deprivation and Repeated Physiological Stress: Implications for Motor Skill Learning and Production. (27th May 2020) - LaFollette, K; Satterfield, B C; Esbit, S; Lazar, M; Grandner, M A; Killgore, W D
Abstract: Introduction: The ability to perform learned motor procedures under stress is a critical skill for many high-risk occupations. Explicit motor skills require top-down cognitive control, which both sleep loss and stress have been found to produce significant degradations, whereas implicit skills rely less on cognitive control and are more resilient to physiological stress. We investigated whether differences in emotion regulation attenuated the effects of sleep deprivation (SD) and acute stress on discrete motor learning. Methods: 45 adults (21 F; 22 ± 3.4 years) participated in 28-hours of in-lab SD. Participants completed repeated batteries that included the Maastricht Acute Stress Test (MAST) Karolinska Sleepiness Scale (KSS), Psychomotor Vigilance Test (PVT), and Discrete Sequence Production Task (DSP). Stress response was quantified by salivary cortisol. We quantified DSP motor performance by total accurate sequences, and average movement time on accurate trials. Ability emotional intelligence (EI) was measured with the MSCEIT, while trait EI was measured with the Bar-On EQI. The CD-RISC was included as a measure of resilience. Results: Using linear mixed effects models of motor performance indices, we found subjective, trait-based emotional intelligence (EQI) to be associated with worse motor performance over time, and objective, ability-based emotional intelligence (MSCEIT) to be associated with greater movement speed. We further found that greater psychological resilience (CD-RISC) but not emotional intelligence was predictive of stronger and less variable chunking structures during SD. Conclusion: Emotional intelligence can influence motor learning under stressful SD, whereas psychological resilience can safeguard learning. Future work should further investigate how trait and ability metrics of EI have opposing effects on responses to stress under SD. Work in this direction could serve to identify difference factors that bolster motor skill production in operational environments where stress and SD are unavoidable. Support: US Army Medical Research and Development Command: W81XWH-17-C-0088